1975
DOI: 10.1037/0097-7403.1.2.149
|View full text |Cite
|
Sign up to set email alerts
|

Frustration and learned helplessness.

Abstract: This article reports the transfer of learned helplessness from one aversive motivator, shock to another, frustration. In experiment 1, animals were trained to approach food in a runway and concomitantly exposed to either escapable, inescapable, or no shock in a different situation. Extinction was conducted in the runway, and subsequently the animals were tested for hurdle-jump escape from the frustrating goal box. Inescapably shocked rats failed to learn to hurdle-jump, whereas escapably or nonshocked animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
16
0
1

Year Published

1978
1978
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 14 publications
5
16
0
1
Order By: Relevance
“…Previously, the intensity of rF-sF was assumed to be a monotonic function of extinction trials (Amsel, 1967;Traupmann, Amsel, & Wong, 1973). However, the findings of an inverted-U function of extinction-induced escape (Rosellini & Seligman, 1975) and aggression (Thompson & Bloom, 1966) are more compatible with the present conception of nonmonotonic function.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…Previously, the intensity of rF-sF was assumed to be a monotonic function of extinction trials (Amsel, 1967;Traupmann, Amsel, & Wong, 1973). However, the findings of an inverted-U function of extinction-induced escape (Rosellini & Seligman, 1975) and aggression (Thompson & Bloom, 1966) are more compatible with the present conception of nonmonotonic function.…”
supporting
confidence: 74%
“…However, a variety of extinction-induced behavior has been reported, such as aggression (Azrin, Hutchinson, & Hake, 1966), agitated behavior (Miller & Stevenson, 1936), escape (Rosellini & Seligman, 1975), displacement activities (McFarland, 1%6), adjunctive drinking (Falk, 1971), sand-digging (Wong, 1977, and response variation (Antonitis, 1951). These phenomena should be taken into account in any viable formulation of experimental extinction.…”
mentioning
confidence: 99%
“…Braud, Wepmann, and Russo (1969) found inescapable shock to interfere with the learning of a response to escape from a coldwater maze. Rosellini and Seligman (1975) reported that inescapable shock interferes with the learning of a hurdle-jump response to escape from frustration. Recently, Goodkin (1976) found that exposure to noncontingent food interferes with the acquisition of a response to escape/avoid shock.…”
mentioning
confidence: 99%
“…For example, if nonresponding is a voluntary instrumental response, then animals presented with noncontrollability (Le., noncontingent food or inescapable shock) should be more resistant to extinction (interference with nonresponding) than animals given controllability or no treatment. However, Rosellini and Seligman (1975) found no effects of controllability of shock on food-reward extinction. Rosellini and Seligman contended that simple exposure to aversive stimulation, whether controllable or uncontrollable, may have resulted in some habituation to the aversive stimulus.…”
mentioning
confidence: 86%
“…In other words, the subjects (Group NC) who received noncontingent reward in the operant chamber (Stage 2) may have learned that their behavior had no control over its consequences or was ineffective in producing consistent rewards. If nonresponding during extinction is a voluntary (learned) response, then Group NC should have shown more resistance to extinction, since studies show that un controllability leads to deficits in instrumental learning in subsequent situations (e.g., Overmier Rosellini & Seligman, 1975;Seligman, 1975;Seligman & Maier, 1967;Wheatley et aI., 1977). The implications of the present results suggest that the learned helplessness model can be extended to predicting performance during extinction.…”
Section: Discussionmentioning
confidence: 99%